Can the patient-reported outcome instruments determine disease activity in rheumatoid arthritis? - Durmus, B.; Altay, Z.; Baysal, O.; Ersoy, Y.; Erdal, A.; Cevik, R.; Ozgocmen, S. (Aepress Sro, 2011)
Objectives: The aim of this study was to investigate the indicative value of the patient-reported outcome instruments (PROs) on disease activity in rheumatoid arthritis (RA). Methods: Three hundred sixty eight patients with RA were included in this cross-sectional study. Disease activity was evaluated using both the Disease Activity Score 28 (DAS 28) and the Clinical Disease Activity Index (CDAI). Patients who had DAS 28 score <3.60 points and CDAI score <10.00 points were allocated into the low disease activity group and those who had DAS 28 score >= 3.60 points and CDAI score >= 10.00 points into the moderate or high disease activity group. The Health Assessment Questionnaire (HAQ), Nottingham Health Profile (NHP), Rheumatoid Arthritis Quality of Life (RAQoL), and Short Form 36 (SF 36) were used as PROs. Logistic regression analysis was used to find variables, which had an indicative value for disease activity. Results: HAQ, pain and emotional reaction subscales of NHP, and bodily pain, general health and social functioning subscales of SF 36 had independent indicative values, when DAS 28 was used as dependent variable. On the other hand, HAQ, pain and emotional reaction subscales of NHP, and general health and emotional role limitation subscales of SF 36 had indicative values when CDAI was used as dependent variable. DAS 28 and CDAI both showed HAQ as the parameter with the highest odds ratio (OR). But RAQoL had shown no independent indicative value for projecting disease activity. Conclusion: It was concluded that HAQ could determine disease activity in RA better than other PROs included in this study (Tab. 4, Ref. 36). Full Text in free PDF www.bmj.sk.
Keywords: disease activity; patient-reported outcome instruments; rheumatoid arthritis; HAQ